Analyzing The Role Of ‘emotional Intelligence’ In Developing Leadership In The Indian Hospitality Sector ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: Emotional intelligence has become a buzz word; Emotional Quotient (EQ) has  long overtaken the Intelligence Quotient (IQ). A manager capable of recognizing and  managing emotions of the self and of others may be more adept at work. Hoteliers have to  work long hours due to which staff may become disgruntled and when insufficient returns are  received, it may show up in their behaviour at work. The hotel industry is a service oriented  industry which has an intangible product to sell, something that is produced and consumed in  the same instant. Objectives: To understand in depth, the concept of emotional intelligence  in hospitality. To analyze the link between EI and its role in developing effective leaders in  hospitality. Methodology: Convenience sampling was used and the samples were  approached online due to COVID. The samples were shortlisted from the personal contacts  of the authors in Hyderabad’s 5 star hotels holding management level positions. Out of 50-60  samples approached, 43 samples consented for their inclusion. Results: EQ has been ignored  in hospitality curriculum with 55% sample base completely agreeing to and same should be  for hiring, as voted by all 43 samples. 26 samples were also in complete favor of EI being a  necessary pre-requisite for promotions. Conclusion: EI is extremely necessary in leader  building and developing EI focused course for the under-graduates will help inculcate the  quality in later stages of career.
Keywords: Emotional Intelligence; Emotional Quotient; Work-life Balance; Hospitality